SIGNOR: A Database of Causal Relationships Between Biological Entities—A Short Guide to Searching and Browsing. Issue 1 (27th June 2017) - Lo Surdo, Prisca; Calderone, Alberto; Cesareni, Gianni; Perfetto, Livia
Abstract: SIGNOR (http://signor.uniroma2.it ), the SIGnaling Network Open Resource, is a database designed to store experimentally validated causal interactions, i.e., interactions where a source entity has a regulatory effect (up‐regulation, down‐regulation, etc.) on a second target entity. SIGNOR acts both as a source of signaling information and a support for data analysis, modeling, and prediction. A user‐friendly interface features the ability to search entries for any given protein or group of proteins and to display their interactions graphically in a network view. At the time of writing, SIGNOR stores approximately 16, 000 manually curated interactions connecting more than 4, 000 biological entities (proteins, chemicals, protein complexes, etc.) that play a role in signal transduction. SIGNOR also offers a collection of 37 signaling pathways. SIGNOR can be queried by three search tools: "single‐entity" search, "multiple‐entity" search, and "pathway" search. This manuscript describes two basic protocols detailing how to navigate and search the SIGNOR database and how to download the annotated dataset for local use. Finally, the support protocol reviews the utilities of the graphic visualizer. © 2017 by John Wiley & Sons, Inc.